Water Quality in Marmara Sea - BOZKURT KOPUZ, ESİN (My University, 2020)
The purpose of the study is to determine the water quality for the continuity of the aquaticlife’ diversity and the health of the citizens and tourists swimming in the Kucuksu, Fenerbahce andSuadiye beaches. Between 5 June 2019 and 29 August 2019, water temperature, pH, dissolved oxygenand salinity were measured weekly onsite and seawater samples were collected to analyze heavy metalconcentrations (Ba, Cr, Mn, Ni, Cu, Zn, Pb, Cd and Se) via ICP-OES. Results showed that values areunder the limits and there is no harm to human health and aquatic life. The measurements were comparedwith the literature data of beaches in the Mediterranean and of the same beaches in the previous studies.